Karakteristik Sifat Mekanis Dan Fisik Tanah Lunak Di Kota Dumai Berdasarkan Pengujian Dokenbo Dan Vane Shear - Muhammad Naufal; Muhamad Yusa; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Soft soil has low shear strength and high compressibility. In this study, portable tools i.e. Dokenbo tool and field Vane Shear were used to determine mechanical characteristics of soft soil quickly and cheaply. Dokenbo is a relatively new field method, developed by the National Institute of Civil Engineering in Japan, to measure shear strength of soft soil. Obtained parameters from Dokenbo are penetration and torsion. This study aimed to determine range of shear strength values from both methods. Correlation of mechanical properties from Dokenbo and Vane Shear was also analyzed. Likewise, correlation between Dokenbo results and soil physical properties. The test was carried out at 3 points field test in Lubuk Gaung Village, Dumai City. From the research, it was obtained that the type of soil was soft soil based on the value of shear strength (Su) with a range of 12-25 kPa. Soil consistency based on the value of penetration resistance is moderately stiff with a value range of 500-1000 kN/m2. Statistical analysis show that penetration value is directly proportional to the Su value, if the penetration value is large, the Su value also increases. Penetration and internal shear angle has a very low correlation. While there is low correlation between penetration and physical properties, where there is no good data connection. Keywords: Soft soil, Shear Strength, Dokenbo, Vane Shear